2022
DOI: 10.3390/genes13122252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiological, and Genetic Characterization of a Patient with a Novel Homoallelic Loss-of-Function Variant in DNM1

Abstract: Heterozygous pathogenic variants in DNM1 are linked to an autosomal dominant form of epileptic encephalopathy. Recently, homozygous loss-of-function variants in DNM1 were reported to cause an autosomal recessive form of developmental and epileptic encephalopathy in unrelated patients. Here, we investigated a singleton from a first-degree cousin marriage who presented with facial dysmorphism, global developmental delay, seizure disorder, and nystagmus. To identify the involvement of any likely genetic cause, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…To conclude, the importance behind the characterization of zebrafish dnm1a gene reported in this paper relies in the fact that zebrafish can be an impressive model not only to deeply understand the involvement of dnm1a in neurodevelopment, but also for the study of pathologic mechanisms related to DNM1 defects. Interestingly, severe neurodevelopmental phenotypes, comprising early‐onset epilepsy, muscular hypotonia, visual impairment, and marked developmental delay, have been described in three patients with DNM1 loss of function mutations (AlTassan et al, 2022; Yigit et al, 2022). Future studies may clarify whether the neurodevelopment defects observed after the dnm1a knockdown precisely recapitulate those in patients, possibly promoting the identification of new therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To conclude, the importance behind the characterization of zebrafish dnm1a gene reported in this paper relies in the fact that zebrafish can be an impressive model not only to deeply understand the involvement of dnm1a in neurodevelopment, but also for the study of pathologic mechanisms related to DNM1 defects. Interestingly, severe neurodevelopmental phenotypes, comprising early‐onset epilepsy, muscular hypotonia, visual impairment, and marked developmental delay, have been described in three patients with DNM1 loss of function mutations (AlTassan et al, 2022; Yigit et al, 2022). Future studies may clarify whether the neurodevelopment defects observed after the dnm1a knockdown precisely recapitulate those in patients, possibly promoting the identification of new therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Among mammalian classical DNMs, DNM1 is the neuron-specific isoform with a pivotal role in synapsis formation and function (Ferguson et al, 2007). Recent studies suggest that mutations in DNM1 gene in mice and humans are associated with neurodevelopmental disorders, as described for other genes involved in synaptic vesicle recycling (AlTassan et al, 2022;Von Spiczak et al, 2017;Yigit et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, 46 patients with epileptic encephalopathy and DNM1 pathogenic variants have been described in 45 families ( 37 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…All missense variants associated with epileptic encephalopathy cluster in the two major functional domains of the DNM1 protein, the GTPase domain, and the middle domain. In addition, homozygous loss-of-function pathogenic variants in DNM1 have been reported to cause a severe autosomal recessive developmental and epileptic encephalopathy in three unrelated patients ( 37 , 41 ). Recurrent DNM1 de novo splice-site variant has also been associated with developmental and epileptic encephalopathy with a dominant-negative mechanism ( 44 ).…”
Section: Discussionmentioning
confidence: 99%